2011
DOI: 10.3109/00365548.2011.600327
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and protein binding of linezolid in cerebrospinal fluid and serum in a case of post-neurosurgical bacterial meningitis

Abstract: We describe a case of bacterial meningitis in a patient administered linezolid (LZD). The ratio of free to total LZD concentrations in cerebrospinal fluid (CSF) was 1 for all measurements, and the LZD concentration in CSF measured at the trough level was almost the same as the free serum concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
0
15
1
Order By: Relevance
“…In this study, the linezolid concentrations in plasma and CSF were much lower than those reported in most other PK studies performed in critically ill patients [12][13][14][15]25].…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…In this study, the linezolid concentrations in plasma and CSF were much lower than those reported in most other PK studies performed in critically ill patients [12][13][14][15]25].…”
Section: Discussioncontrasting
confidence: 63%
“…In one case study of linezolid in meningitis, the authors reported similar drug concentrations in plasma and CSF and suggested that plasma concentrations are a suitable indicator of CSF penetration [15]. This is unsurprising as drug penetration in meningitis should be greater than in patients with non-inflamed meninges.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Linezolid has been shown to have good penetration into the CSF 61,117. Linezolid has also been used to treat CNS infections caused by resistant organisms, including by VRE118 and by PRP,119 including treatment of PRP after failure of vancomycin 120.…”
Section: Efficacy Studiesmentioning
confidence: 99%